Management of Industrial Wastewater Quality Using IoT - Morsi, Moamen A.; Youssef, Yehia M.; Hassan, Mohamed K. (Journal of Industrial Engineering & Management Research, 2024)
Industrial wastewater treatment should be the focus of any industry using water to decrease the dependency on the scarce fresh water and to guarantee a safe disposal of the treated water. Wastewater treatment requires tailored processes based on the desired input wastewater quality measured by parameters such as pH, TDS, and turbidity and the desired application of the treated water. Wastewater properties vary by source, such as municipal, industrial, agricultural, and household, with the industrial wastewater being the most polluted. Water quality standards are set by organizations like the World Health Organization (WHO) and the Ministry of Environment in each country. This work proposes a system that involves a smart water quality management system using Internet of Things (IoT) devices such as sensors for real-time monitoring and actuators for controlling the water quality. This system treats the output wastewater from a detergent production line through sedimentation and filtration. Key water quality parameters: pH, TDS, and turbidity are monitored and controlled to meet the Egyptian Ministry of Environment's standards for disposal into Nobaria Canal. The treated water can be reused in applications like production lines, firefighting, or irrigating of ornamental plants. The system is programmed with Arduino software, and sensor data is displayed using Realterm software.